ETHNIC STEREOTYPES OF THE VOLGA TATARS IN ORDINARY LANGUAGE CONSCIOUSNESS OF RUSSIANS AND THE TATARS OF THE REPUBLIC OF TATARSTAN - Razumkova, A.V. (RUDN Journal of Language Studies, Semiotics and Semantics, 2017)
In the article, based on the interpretation of the experimental material, the content of the ethnic image of the Volga Tatars is determined. The relevance of the study is explained by the fact that the description of the content of the images: “yourself” and “the other” in the minds of Russians and the Tatars can make a significant contribution to the work on forecasting and research of interethnic tension in the Re-public of Tatarstan. The object of the study is the ethnic image of the autochthonous population of the Repub-lic of Tatarstan. The subject of the research is auto- and heterostereotypes of the Volga Tatars within the framework of the “national character” domain. The study of ethnic stereotypes implies the research of de-scriptive features on the material of the associative field “Tatars, what are they? (give some certain typical features)”, which is analyzed with the help of the methodology of field stratification techniques that was developed by I.A. Sternin and A.V. Rudakova (2011). The method of constructing the “semantic gestalt” proposed by Yu.N. Karaulov (2000) was used for the analysis of the ethnonyms. The material for describing the auto- and geterostereotypes of the Volga Tatars was collected with the help of the directed associative experiment, which was conducted among students (17-23 years) of higher educational establishments in Kaluga and Kazan in 2016. The associative field of the ethnonym “Tatars” was formed on the base of the pilot free associative experiment conducted in Russian among schoolchildren and students (12-23 years) of the Republic of Tatarstan in 2015. Comparison of the results of two psycholinguistic experiments allows us to conclude that most of the ethnostereotypes occupy the periphery of the image of the ethnos. In general, the research testifies that Russians and the Tatars of the Republic of Tatarstan perceive the Tatars in a non-stereotyped way.